2007
DOI: 10.1185/030079907x182239
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a paracetamol and caffeine combination in the treatment of the key symptoms of primary dysmenorrhoea

Abstract: When taken at recommended doses, both paracetamol and the combination of paracetamol and caffeine are safe and effective treatments for primary dysmenorrhoea. Consistent with results from other acute pain states, caffeine acts as an analgesic adjuvant and enhances the efficacy of paracetamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Time effect curves for pain were presented in all four of the papers [43–46]. The dysmenorrhea study showed a statistically significant difference in favor of the combination at 30 minutes after dosing ( P < 0.05) and this difference was maintained for the duration of the study [43]. Similar results were observed in the combined analysis of two studies in headache patients [44] and in each of the four studies presented by Laska et al.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Time effect curves for pain were presented in all four of the papers [43–46]. The dysmenorrhea study showed a statistically significant difference in favor of the combination at 30 minutes after dosing ( P < 0.05) and this difference was maintained for the duration of the study [43]. Similar results were observed in the combined analysis of two studies in headache patients [44] and in each of the four studies presented by Laska et al.…”
Section: Resultssupporting
confidence: 70%
“…All of the eight studies included in the meta‐analysis provided efficacy results as mean TOTPAR values over 0–4 hours [43–46]. In the four studies reported by Laska et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With specific relevance to paracetamol plus caffeine vs. paracetamol alone, the relative potency estimate was 1.37 [13]. More recent clinical studies on adjuvant actions of caffeine suggest that caffeine was useful for enhancing relief of headache pain [14][15][16] and menstrual pain [17].…”
Section: Discussionmentioning
confidence: 99%
“…Since her menarche began, she had taken at least 2 caplets of pain relievers (each contains 500 mg of acetaminophen and 65 mg of caffeine) without exception to maintain her normal lifestyle during menstrual periods, which happened to be the dose recommended by a previous report (1 g of acetaminophen and 130 mg of caffeine). 24 The symptoms of dysmenorrhea usually accompanied the start of menstrual flow and lasted for about 3 days, with intensity peaking on the second day. Associated symptoms included diarrhea (once on the first day of each menstrual period), referred lower back pain, and fatigue.…”
Section: Case Reportmentioning
confidence: 99%